Auction based bandwidth allocation mechanism for P2P content distribution networks - Yun-he ZHANG; Yan-qin ZHU; Qi-jin JI (Tongxin xuebao)
Unreasonable allocation of originally scarce bandwidth was a severe problem in the P2P content distribution networks.To solve the problem and suppress the node's selfishness,an auction-based bandwidth allocation mechanism for P2P networks was proposed.Through the effective bandwidth payment scheme,the selfish nodes had no incentives to lie and provided the real bandwidth requirements.Also the “tragedy of the commons” could be avoided by the nodes' healthy bandwidth competition.To adapt to the distributed nature of the P2P networks,the algorithm was implemented in parallel at resource providing nodes and request nodes.Simulation results show that the scheme not only suppresses riding nodes efficiently in the system,but also shortens the average completion time for content distribution and decreases the ratio of data uploaded by the source server.